The Impact of Servant Leadership, Supervision Competence, and Teacher Performance on School Quality - Waldatun Thai' Atun; M. Syadeli Hanafi; Nandang Faturohman; Suryadi Suryadi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study examines the correlation between servant leadership, supervisory competency, and teacher performance in school quality. Method: The results of this investigation were confirmed by employing a statistical survey approach. The structural equation model's PLS-SEM method for prediction was used to generate the values of the latent variables. The research sample comprised nineteen principals and two hundred thirty-one elementary school teachers from the Ciwandan sub-district of Cilegon City in Banten Province. Results: Structural model statistical studies show a positive relationship between servant leadership and supervisory competence. Supervision competency and school quality are not positively correlated. Servant leadership is positively correlated with teacher performance, and teacher performance is positively correlated with school quality. Novelty: The novelty of this research is that there are differences in emphasis, research participants, and integration of research components compared to other research. This study introduces novel research integrating servant leadership, supervisory competency, and teacher performance in school quality. This innovative research integrates multiple variables into a single unit for investigation and analysis.